Diagnostic performance of DNA index for detection of high hyperdiploidy in childhood B-cell acute lymphoblastic leukemia - César Rivera-Orcoapaza; Jaime Rosales-Rimache (PLoS ONE, 2026)
Introduction High hyperdiploidy (HHD) is the most common cytogenetic abnormality in childhood B-cell acute lymphoblastic leukemia (B-ALL) and is a pivotal finding for prognosis evaluation and treatment stratification. Karyotyping is considered the gold standard for detecting HHD; however, cytogenetic cultures sometimes fail. The DNA index (DI) analysis by flow cytometry (FCM) is a quick and simple approach to estimating HHD without the need for cultures. The aim of this study was to assess the diagnostic performance of DI for detecting HHD in pediatric patients with B-ALL. Methods A cross-sectional study was conducted on 210 pediatric patients with B-ALL at Instituto Nacional de Salud del Niño San Borja (INSNSB) in Peru between 2017 and 2021. The receiver operating characteristic (ROC) curve was analyzed using karyotype results as the reference standard to determine the optimal DI cut-off value for HHD. The main diagnostic performance indicators were subsequently described. Immunophenotypic characteristics associated with HHD were also explored using a generalized linear model (GLM). Results A 25.2% (n = 53/210) rate of failed karyotypes was observed. DI ≥ 1.10 showed a sensitivity of 96.6% (95% CI: 93.7–99.4%), specificity of 89.8% (95% CI: 85.1–94.6%), positive predictive value of 68.3% (95% CI: 61.0–75.6%), negative predictive value of 99.1% (95% CI: 97.7–100.0%), and AUC of 0.947 (95% CI: 0.914–0.980). The overall concordance between DI and karyotype was 91.1% (n = 143/157), with a Kappa index 0.75 (95% CI: 0.62–0.87). Blast size (PR = 4.8, 95% CI: 2.7–8.5) and CD123 expression (95% CI: 1.9–73) were associated with HHD (p < 0.001 and p < 0.009, respectively). Conclusion DI has a high diagnostic performance and is helpful as a complementary method to karyotyping for detecting HHD.